PELATIHAN PEMBENTUKAN KARAKTER ANAK BANGSA: TALK SHOW HARI KEBANGKITAN NASIONAL INDONESIA - Elvyani Nuri Harlawati Gaffar; Ivana Nina Esterlin Barus; Emmilya Umma Aziza Gaffar; Revalia Wijaya; M. Fery Fahrullah; Muhammad Riki Maulana (Jurnal Pengabdian kepada Masyarakat, 2025)
The role of academics and practitioners is essential in increasing national awareness, national spirit, and active participation of youth. Academics from the University of August 17, 1945 Samarinda, Mulawarman University, and practitioners in collaboration with Islamic Center TV East Kalimantan conducted community service activities to provide understanding, increase enthusiasm, and national commitment among the younger generation of Indonesia. The purpose of this activity was to measure the extent to which the National Awakening Day talk show contributed to an increased “sense of belonging” and understanding of the younger generation of the values of national awakening. The method used was an interactive discussion guided by a moderator and featuring resource persons who are experts in their respective fields. Participants in the activity were students of the University of August 17, 1945 Samarinda, and all viewers who watched the talk show via live streaming on the Islamic Center TV East Kalimantan. The results of the activity for the participants were gaining an understanding of character as the initial foundation of the nation and state, how to address the character of the Indonesian nation today so as not to be influenced by negative things originating from broadcasts on social media, and the role of universities in being able to shape students to have noble morals.